DEMYSTIFYING THE MYTHS ASSOCIATED WITH PLACEMENTS - Thomas, Shobin; A, Stalin (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
The aim of this study is to find out the myths related to the perception and the challenges of campus placements by management professionals during their final year at b-schools. Campus recruitment provides a platform for the organizations to meet the aspirants and pick up intelligent, committed youth from various colleges and educational institutes who have the requisite enthusiasm and zeal to prove themselves. In order to find the right candidates, organizations employ various recruitment and selection procedures. With the advancement of technology, the need for talented and self-motivated young people who can work tirelessly has grown. Thus, organizations do not confine themselves to only the selected institutes but spread their net far and wide. This study was done at selected b-schools which have good placement track records. The research gives importance to various activities involved in campus recruitment and sees how much the candidate is aware of the recruitment. It also includes the candidate’s viewpoint on job vacancies and the interview challenges they faced. This research is based on the primary data which was collected as per the sample size which is 39. The study concluded with findings and suggestions that would help to know the challenges faced by management professionals during the time of campus placements